2007
DOI: 10.1152/ajpgi.00474.2006
|View full text |Cite
|
Sign up to set email alerts
|

Altered protein expression at early-stage rat hepatic neoplasia

Abstract: Protein expression patterns were analyzed in a rat model of hepatic neoplasia to detect changes reflecting biological mechanism or potential therapeutic targets. The rat resistant hepatocyte model of carcinogenesis was studied, with a focus on the earliest preneoplastic lesion visible in the liver, the preneoplastic hyperplastic nodule. Expression differences were shown by two-dimensional polyacrylamide gel electrophoresis and image analysis. Polypeptide masses were measured by peptide mass fingerprinting usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 66 publications
(83 reference statements)
1
11
0
Order By: Relevance
“…The gene transfer of SERPINA4 was also found to suppress angiogenesis and metastasis in a hepatocellular carcinoma mouse model (30, 31) and in a gastric cancer mouse model (32). The decreased levels of SERPINA4 have also been reported in hepatocellular carcinoma tissue samples compared with normal liver tissue samples as indicated by two dimensional gel electrophoresis with proteomics analysis (33). Our data indicate a mild increase of SERPINA4 protein levels in SCLC samples and a more prominent increase of the fucosylated SERPINA4 form.…”
Section: Discussionmentioning
confidence: 89%
“…The gene transfer of SERPINA4 was also found to suppress angiogenesis and metastasis in a hepatocellular carcinoma mouse model (30, 31) and in a gastric cancer mouse model (32). The decreased levels of SERPINA4 have also been reported in hepatocellular carcinoma tissue samples compared with normal liver tissue samples as indicated by two dimensional gel electrophoresis with proteomics analysis (33). Our data indicate a mild increase of SERPINA4 protein levels in SCLC samples and a more prominent increase of the fucosylated SERPINA4 form.…”
Section: Discussionmentioning
confidence: 89%
“…Recent findings have indicated that kallistatin may play an important role in the protection against oxidative stress-induced inflammatory responses and organ damage. In a highly reproducible rat resistant hepatocyte model, kallistatin was not detectable or at very low levels in nodule tissue compared with normal liver by proteomics study [26]. A significantly reduced kallistatin level was seen in plasma samples from patients with chronic, severe liver disease [27], suggesting that kallistatin is produced mostly in the liver and can be consumed during inflammation in the liver.…”
Section: Discussionmentioning
confidence: 96%
“…The strip was focused in an IPGphor isoelectric focusing system (GE Healthcare Biosciences AB). The proteins were diffused into the strip using active rehydration, and isoelectric focusing occurred overnight with a total voltage-hours of approximately 15 kV ⅐ h. The isoelectric focusing gel strips were rehydrated, equilibrated, and stained as previously described (20). The strip was overlaid on a 13% SDS-PAGE gel and was run until the dye front reached the bottom of the gel.…”
Section: Methodsmentioning
confidence: 99%